(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
Food is required for the survival of all living organisms. Foods include a variety of nutrients such as carbs, lipids, proteins, vitamins, and minerals. An organism consumes and digests these nutrients in order to generate energy, which is needed to promote development and sustain regular living processes. Food spoilage can be caused by environmental or food-borne chemical, enzymatic, as well as occurs when the bacteria. Food has a finite shelf life; preservative are used in food to enhance that shelf life or preserve quality; nevertheless, these preservatives may have certain detrimental side effects. As both a result, today’s consumer demand for minimally processed foods devoid of chemical preservatives has fueled interest in biology alternatives. By preventing or inhibiting growth of microorganisms, processed foods are substances found in food, pharmacological dosage forms, but rather cosmetic planning and preparation to maintain product accuracy and reliability, increase and otherwise preserve nutrient advantage, maintain edibility but also wholesomeness, start providing leavening (yeast), control pH, enhance flavour, or provide colour. A good preservative must be effective at low levels, non-toxic, generally compatible with all the other components in the recipe, as well as stable throughout the shelf life of the recipe. This review article examines the use of natural food preservatives as an alternative to artificial preservatives for a better human diet.